Analisis Pengaruh Perputaran Piutang terhadap Profitabilitas pada PT PDAM Tirtanadi Tapanuli Selatan - Ginting, Wira Hamdani (YASIN, 2023)
Receivables are working capital that is always rotating, the time for collecting receivables is seen from the turnover of receivables into cash in one year. The profitability of a company can be measured using gross profit margin and return on assets. GPM is the company's ability to make the cost of revenue effective to generate profits in its operational activities. Meanwhile, ROA shows the company's effectiveness in managing all its assets to generate profits in operational activities. The aim of this research is to determine and analyze the effect of accounts receivable turnover on profitability as measured by GPM and ROA. The research object is PT. PDAM Tirtanadi South Tapanuli branch for the period 2006 - 2013. This type of research is associative with data analysis techniques using non-parametric statistical analysis with the help of SPSS 18.0 software. The results of this research show that the receivables turnover variable has a significant influence on gross profit margin. The results of this research are strengthened by the results of hypothesis testing through the Kendall test of 0.01 and the Spearman test of 0.00 which shows the significance of the receivables turnover rate being below 0.05, which means the receivables turnover rate has a significant effect on profitability (GPM). Meanwhile, the research results of the receivable turnover variable do not have a significant effect on return on assets. These results can be seen by the results of hypothesis testing via the Kendall test of 1.00 and the Spearman test of 1.00 which shows the significance of the receivables turnover rate being above 0.05, which means the receivables turnover rate has no significant effect on profitability (ROA).